FRWSC: a framework for robust Web service composition. Issue 4 (December 2016) - El Kholy, Mohamed; El Fatatry, Ahmed
Abstract The deployment of Web services in a highly dynamic environment brings about a number of research challenges. In dynamic Web services composition, failures and changes to atomic services cannot be detected before invocation. Hence, the failure or even the change in an atomic service may lead to the overall failure of the composite service. In addition, SOAP error code is not sufficient for the client to analyze the failure reason and handle it. In this work, we introduce a framework to deal with unexpected failures during runtime composition. The proposed framework is built on top of composite services stack as an interface between the composite service and its external service partners. The evaluation results show that by using the proposed framework, it is possible to avoid composite service failures that are caused by changes or failures in atomic services.